Refugee Entrepreneurship - Joseph Dushime; Stephen Muathe (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This paper sought to examine the multifaceted term refugee entrepreneurship from a global level, to a more focused view of the Kenyan context. As such, the authors of this paper examined the general understanding of refugee entrepreneurship in Kenya, assessed the effect of talent displacement with regards to refugee entrepreneurship in Kenya and analyzed the effect of integration and social economic inclusion in relation to refugee entrepreneurship in Kenya. Design/methodology/approach: The paper utilized qualitative research where available secondary data on refugee entrepreneurship was analyzed. Findings: The study found that there appeared to be no clear-cut understanding of refugee entrepreneurship in the Kenyan context, no systematic approach to tackle talent displacement with regards to refugee entrepreneurship in Kenya, and there continued to be barriers to full integration and social economic inclusion with regards to refugee entrepreneurship in Kenya. Research limitations/implications: This study also noted that there is no current global solution to the issue of the ever-increasing number of internally displaced persons, asylum seekers or refugees. On the contrary, the year 2022 has seen an increase in civil strife around the world including; the Russia-Ukraine conflict, Tigray-Ethiopia war and the more than 20-year-old ongoing conflicts in Eastern Democratic Republic of Congo. Other conflicts of concern on the African continent include; South Sudan, Somalia, Mozambique and other West African nations, while Libya and other North African states have suffered similar civil strife. Despite these ongoing challenges, this study established that there are significant socio-economic contributions of refugee entrepreneurship to host communities. Practical implications: Consequently, the study recommended a more in-depth understanding of refugee entrepreneurship in the context of Kenya, nurture refugee talents and skills while enacting and enabling policies that foster integration and social economic inclusion with regards to refugee entrepreneurship in Kenya. The Government and people of Kenya stand to reap the benefits of refugee entrepreneurship, which in turn reduced refugee talent displacement and continued government handouts that have promoted dependency, rather than self-reliance. Refugee entrepreneurship, if well cultivated, is an avenue for adding to Kenya’s bread basket through taxation, employment and investment. Paper type: Research paper